A PILOT STUDY ON THE EFFICACY OF SIDDHA MEDICINE SEENTHIL SARKARAI IN THE MANAGEMENT OF MOOTHIRAKIRICHARAM (URINARY TRACT INFECTION) - V, *Elakkiyaa; T, Arulmozhi; S, Visweswaran; S, Sivakkumar; A, Mariappan; V, Banumathi (International Journal of Ayurveda and Pharma Research, 2018)
Objective: The present pilot study was designed to evaluate the efficacy of Seenthil sarkarai, a Classical Siddha medicine in Moothirakiricharam (Urinary Tract Infection) patients. Method: This study was approved by IEC and registered in Clinical Trial Registry of India and was conducted at the National Institute of Siddha, Tambaram, Chennai, India. The investigator recruited 20 patients of both male and female with an inclusion and exclusion criteria. All the patients were treated with Seenthil Sarkarai at the dose level of 2 grams two times a day with warm water for 21 days. Dietary regimen was advised for the patients. Study outcome was studied with negative Urine culture and also based on the improvement in the reduction of Burning micturition, Frequency of micturition, Dysuria with fever, Foul smelling urine. Results: The symptoms such as burning micturition, persistent urge to urinate, foul smelling urine, and presence of bacteriuria reduced markedly within 21 days of duration. Out of 20 patients, 12 patients were completely relieved from the compliance of UTI with negative Urine culture. The symptoms of UTI were markedly reduced in remaining 8 patients. There were no adverse effect reported during the study and no recurrence of UTI was noticed in 12 patients who were completely cured. Conclusion: Results suggest that the trial drug Seenthil Sarkarai is effective and safe for the management of Moothirakiricharam (UTI) and in alleviating recurrences.